Effect of CTAB Templating on Mesoporous SiO₂from Rice Husk on the Adsorption of Methylene Blue - Melisa Nur Kibtiah; Rahmad Nuryanto; Yayuk Astuti (Universitas Diponegoro, 2026)
Water contamination caused by dye-containing industrial effluents remains a significantenvironmental concern, necessitating the development of efficient and sustainable treatmenttechnologies. This study investigated the effect of cetyltrimethylammonium bromide (CTAB) as astructure-directing agent on the meso-structural properties and adsorption performance of ricehusk-derived mesoporous SiO2 toward methylene blue (MB). Mesoporous silica was synthesizedhydrothermally using sodium silicate extracted from rice husk, both in the absence and presenceof CTAB, yielding materials denoted as MS and MS-CTAB, respectively. Structuralcharacterization revealed that CTAB-assisted synthesis significantly enhanced the texturalproperties of the material, resulting in a higher specific surface area (580.38 m2/g) compared toMS (89.63 m2/g), along with improved pore uniformity and accessibility. These structuralimprovements facilitated superior adsorption performance, with MS-CTAB achieving an MBremoval efficiency of 86.02 %, compared to 74.19 % for MS. Adsorption kinetics were betterdescribed by the pseudo-second-order model, while equilibrium data were more accurately fittedby the Langmuir isotherm model, with a maximum adsorption capacity of 63.29 mg/g. Thefindings demonstrate that CTAB-assisted hydrothermal synthesis effectively improves themesostructural characteristics and adsorption efficiency of rice husk-derived SiO2, highlightingits potential as a sustainable adsorbent for dye removal from aqueous media.